Nerve transfer with 3D-printed branch nerve conduits. Issue 1 (15th April 2022) - Zhang, Jing; Tao, Jie; Cheng, Hao; Liu, Haofan; Wu, Wenbi; Dong, Yinchu; Liu, Xuesong; Gou, Maling; Yang, Siming; Xu, Jianguo
Abstract: Background: Nerve transfer is an important clinical surgical procedure for nerve repair by the coaptation of a healthy donor nerve to an injured nerve. Usually, nerve transfer is performed in an end-to-end manner, which will lead to functional loss of the donor nerve. In this study, we aimed to evaluate the efficacy of 3D-printed branch nerve conduits in nerve transfer. Methods: Customized branch conduits were constructed using gelatine-methacryloyl by 3D printing. The nerve conduits were characterized both in vitro and in vivo . The efficacy of 3D-printed branch nerve conduits in nerve transfer was evaluated in rats through electrophysiology testing and histological evaluation. Results: The results obtained showed that a single nerve stump could form a complex nerve network in the 3D-printed multibranch conduit. A two-branch conduit was 3D printed for transferring the tibial nerve to the peroneal nerve in rats. In this process, the two branches were connected to the distal tibial nerve and peroneal nerve. It was found that the two nerves were successfully repaired with functional recovery. Conclusions: It is implied that the two-branch conduit could not only repair the peroneal nerve but also preserve partial function of the donor tibial nerve. This work demonstrated that 3D-printed branch nerve conduits provide a potential method for nerve transfer.